Assistance for legislative drafting in the Caribbean - Pollard, Brynmor (Commonwealth Secretariat LondonGB, 1995)
Seeks to assess the efficiency, effectiveness and impact of the technical assistance programme in the field of legislative drafting, the contribution made by the Commonwealth Fund for Technical Cooperation (CFTC) and to determine the lessons learned which would be of value for future programmes of assistance including those to regional educational institutions within and outside the Caribbean. Covers the period 1986 to 1993 and focuses mainly on the Legislative Drafting Training Programme conducted at the Cave Hill Campus of the UWI.